Dermoid cyst associated with segmental multicystic renal dysplasia: A rare case - Syrine Laribi; Marwa Messaoud; Manel Njima; Mabrouk Abdelali; Samia Belhassen; Afef Toumi; Mongi Mekki; Lassaad Sahnoun (Urology Case Reports)
Most multicystic dysplastic kidneys (MCDKs) are detected prenatally, yet there is no clear consensus on initial evaluation and follow-up. We report the case of a 4-year-old male diagnosed with right pyelocalyceal dilation in utero, confirmed postnatally as MCDK. Follow-up ultrasounds revealed rapid growth of three upper pole cysts, reaching 8 cm. A right upper pole nephrectomy was performed, and histopathology revealed a renal dermoid cyst within segmental multicystic renal dysplasia. This case highlights the critical role of postnatal imaging and follow-up in detecting atypical features, including rare entities like intrarenal teratomas, enabling timely surgical intervention and improved outcomes.